2020
DOI: 10.4236/fns.2020.1110065
|View full text |Cite
|
Sign up to set email alerts
|

Salt/Sodium Intake Estimation in Children and Adolescents of Costa Rica

Abstract: The objectives of this study were to estimate sodium intake and to identify the main dietary sources of this nutrient in young people. Cross-sectional study performed in 2685 students from 64 schools and high-schools of Costa Rica. A food frequency survey was applied to study the food and beverage intake habits of the participants. The average daily sodium intake for children and adolescents 7 to 18 years of age was 3214 mg. Around 97% of the students had sodium intakes > 2300 mg per day with significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Studies involving people with hypertension showed that although the respondents were aware of the recommendations to reduce the consumption of salt, most of them exceeded the recommended levels [ 48 ]. Children and adolescents also consume too much salt—on average, more than 3 g a day [ 49 , 50 ]. As early as 2006, the World Health Organization recommended that the daily intake of Na should not exceed 2 g, which is an amount contained in 5 g of table salt, to reduce the risk of cardiovascular diseases [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving people with hypertension showed that although the respondents were aware of the recommendations to reduce the consumption of salt, most of them exceeded the recommended levels [ 48 ]. Children and adolescents also consume too much salt—on average, more than 3 g a day [ 49 , 50 ]. As early as 2006, the World Health Organization recommended that the daily intake of Na should not exceed 2 g, which is an amount contained in 5 g of table salt, to reduce the risk of cardiovascular diseases [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium available for consumption in national households largely exceeded the intake levels recommended by the World Health Organization (<2 g sodium/person/day) and increased between 2005 and 2013 from 3.9 to 4.6 g/per adult person/day (p < 0.001) [12]. The estimated mean sodium intake in Costa Rican children and adolescents from 7 to 18 years of age, based on a food frequency survey and added salt to the served food, was 3.4 g with a sodium density of 1.8 g of sodium/1000 kcal, maintaining significant differences by age subgroups (p < 0.001) [13].…”
Section: Introductionmentioning
confidence: 86%
“…In many European countries, due to a lack of time, homemade meals are rare, so only a small percentage of sodium intake derives from salt added in cooking [ 4 ]. More than one-third (34%) of Swiss children reported adding salt to their meals on the plate [ 58 ], but this figure was even higher for Costa Ricans (49.4%) [ 78 ]. In the quoted study, nearly 39% of the participants said they usually add at least one pinch of salt to their meals one or two times a week; in turn, one in ten children from Costa Rica declared that they added a pinch of salt even three or four days in a week.…”
Section: Sources Of Salt In the Human Dietmentioning
confidence: 99%